Wielowymiarowa analiza oczekiwań klientów wobec dystrybutorów produktów leczniczych - Stanimir, Agnieszka; Sieińska, Anna (Multidimensional Analysis of Customers' Expectations Towards Medical Products Distributors, 2007)
Pharmaceutical wholesale firms, pharmacies and other retailers, matter fundamentally in medical products supply system. The aim of this article is to analyze the situation in pharmaceutical sector and point main expectations of customers towards medical products distributors. The correspondence analysis is used to show results of comparison in multidimensional form.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 89-100